"A Game Without Competition Is Hardly a Game": The Impact of Competitions on Player Activity in a Human Computation Game" - Reeves, Neal; West, Peter; Simperl, Elena (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2018)
Virtual citizen science (VCS) projects enable new forms of scientific research using crowdsourcing and human computation to gather and analyse large-scale datasets. To attract and sustain the number of participants and levels of participation necessary to achieve research aims, some VCS projects have introduced game elements such as competitions to tasks. However, we still know very little about how some game elements, particularly competitions, influence participation rates. To investigate the impact of game elements on player engagement, we conducted a two-part mixed-methods study of EyeWire, a VCS game. First, we interviewed EyeWire designers to understand their rationale for introducing competitions. Guided by their answers, we analysed two datasets of EyeWire user task contributions and chat logs to assess the effectiveness of competitions in achieving designers' goals. Our findings contribute to the growing understanding of how competitions influence participant activity in human computation initiatives and socio-technical systems such as VCS.